Tumor Necrosis Factor-Induced Cytotoxicity is Not Related to Rates of Mitochondrial Morphological Abnormalities or Autophagy-Changes that can be Mediated by TNFR-I or TNFR-II. Issue 6 (December 1998) - Prins, Johannes B.; Ledgerwood, Elizabeth C.; Ameloot, Paul; Vandenabeele, Peter; Faraco, Paulo R.; Bright, Nicholas A.; O'Rahilly, Stephen; Bradley, John R.
Abstract : Tumor necrosis factor (TNF) may cause apoptosis or necrosis and induces mitochondrial changes that have been proposed to be central to cytotoxicity. We report similar patterns of TNF-induced mitochondrial morphological alterations and autophagy in cell types with differing sensitivity to TNF-induced cytotoxicity. Specific ligation of TNFR-I or TNFR-II induces different rates of apoptosis and mitochondrial morphological change, but similar rates of autophagy. These changes do not invariably lead to cell death, and survival or progression to apoptosis or necrosis following TNF exposure may depend in part on the extent of mitochondrial damage and/or the autophagic capacity of the cell.